Inverse kinematics of six degrees of freedom robot manipulator based on improved dung beetle optimizer algorithm - Haohao, Ma; As’arry, Azizan; Haoyang, Zhang; Ismail, Mohd Idris Shah; Ramli, Hafiz Rashidi; Zuhri, Mohd Yusoff Moh; Delgoshaei, Aidin (Intelektual Pustaka Media Utama, 2024)
Inverse kinematics is a basic problem in robotics, which aims to solve the robot’s joint angles according to the end effector’s position and orientation. This paper proposed an improved spiral search multi-strategy dung beetle optimizer (DBO) algorithm for solving the inverse kinematics problem. The improved DBO algorithm considers not only the error between the target value and the current value but also the previous position of the robot to ensure minimum displacement during the movement. To solve the end position error and orientation error of the robot end effector more accurately, the quaternion is introduced as a penalty factor in the optimization objective function, which is of great significance for reducing the orientation error. Through the improved DBO algorithm, the position error is still accurate, and the orientation error is reduced from 9.5901 to 1.8718. Experimental results show that the proposed algorithm outperforms other swarm-intelligent algorithms in terms of accuracy and convergence speed. Overall, the proposed spiral search multi-strategy DBO algorithm provides an effective and efficient solution to the inverse kinematics problem in robotics.